Serial Subtraction Alters Lateral Step-down Tibiofemoral Kinematics in Healthy Adults - Thomas, Jacob; Weiss, Samantha; Bliss, Rebecca; Guess, Trent (International Journal of Sports Medicine, 2023)
This study evaluated the effects of two types of cognitive dual-tasking on three-dimensional knee kinematics during the lateral step-down. 19 healthy individuals (22.05±1.61 yrs., 173.92±9.21 cm, 67.99±12.65 kg) participated in this study. Participants completed 5 repetitions of a lateral step-down task for each leg and each testing condition (control, Stroop, and serial subtraction by seven). An electromagnetic motion sensor was attached to the femur via compression clamp placed about the medial and lateral epicondyles. Another sensor was attached 2 cm below the ipsilateral tibial tuberosity. A custom MATLAB algorithm located the knee joint axis of rotation from dynamic knee flexion and extension. Discrete kinematics at peak flexion were used in this study. Paired samples t-tests were used to compare average frontal, transverse, and sagittal plane knee position at maximum flexion between conditions for each leg. No significant differences were found for either limb between control and Stroop conditions. Comparisons revealed significant differences in frontal and transverse plane knee angles at peak flexion between the control and serial subtraction by seven conditions. These findings indicate serial subtraction by seven requires different cognitive processing abilities which may cause greater interference with some aspects of motor control.
Keywords: dual-task; stroop; biomechanics; cognitive; motor